2013
DOI: 10.1126/scisignal.2004184
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cl Channel ANO1 by Localized Calcium Signals in Nociceptive Sensory Neurons Requires Coupling with the IP 3 Receptor

Abstract: We report that ANO1 (also known as TMEM16A) Ca 2+ -activated Cl − channels in small neurons from dorsal root ganglia are preferentially activated by particular pools of intracellular Ca 2+ . These ANO1 channels can be selectively activated by the G protein-coupled receptor (GPCR)-induced release of Ca 2+ from intracellular stores, but not by Ca 2+ influx through voltage-gated Ca 2+ channels. This ability to discriminate between Ca 2+ pools was achieved by the tethering of ANO1-containing plasma membrane domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
222
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 176 publications
(239 citation statements)
references
References 61 publications
15
222
2
Order By: Relevance
“…Our data suggest that in sensory neurons ANO1 may physically interact with the IP 3 R (Jin et al . 2013), but we do not yet know if these interactions are direct nor if they are constitutive. Likewise, we do not yet know what other components exist within such signalling complexes or what interactions hold these together.…”
Section: Ano1 Containing Signalling Complexes: Future Perspectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…Our data suggest that in sensory neurons ANO1 may physically interact with the IP 3 R (Jin et al . 2013), but we do not yet know if these interactions are direct nor if they are constitutive. Likewise, we do not yet know what other components exist within such signalling complexes or what interactions hold these together.…”
Section: Ano1 Containing Signalling Complexes: Future Perspectivesmentioning
confidence: 99%
“…2010; Jin et al . 2013). Thus, in patch‐clamp recordings from cultured capsaicin‐sensitive DRG neurons we found that activation of VGCCs with voltage pulses rarely resulted in a CaCC current activation, even in same neurons in which B 2 or PAR‐2 receptor triggering did activate CaCCs (Jin et al .…”
Section: Coupling Between Ano1 and Endoplasmic Reticulum; Is This A Gmentioning
confidence: 99%
See 3 more Smart Citations